BV Solutions to a Degenerate Equation Coupled with Time-delay Regularization (Journal of Partial Differential Equations, 2020)
In this paper, we study a initial value problem of a degenerate parabolic equation coupled with time-delay regularization. The existence of BV solutions to the problem for an initial BV_{loc} data is obtained. Moreover, the existence and uniqueness of spatial-periodic classical solutions to its corresponding regularized problem are also given.